U. S. Grant : American Hero, American Myth - Waugh, Joan (Book collections on Project MUSE., 2009)
At the time of his death, Ulysses S. Grant was the most famous person in America, considered by most citizens to be equal in stature to George Washington and Abraham Lincoln. Yet today his monuments are rarely visited, his military reputation is overshadowed by that of Robert E. Lee, and his presidency is permanently mired at the bottom of historical rankings. Joan Waugh uncovers the reasons behind the rise and fall of Grant's renown, underscoring as well the fluctuating memory of the Civil War itself.